2022
DOI: 10.1007/s00216-022-04449-x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the screening of antimicrobial compounds using electrochemical biosensors: is there room for nanomaterials?

Abstract: The abusive use of antimicrobial compounds and the associated appearance of antimicrobial resistant strains are a major threat to human health. An improved antimicrobial administration involves a faster diagnosis and detection of resistances. Antimicrobial susceptibility testing (AST) are the reference techniques for this purpose, relying mainly in the use of culture techniques. The long time required for analysis and the lack of reproducibility of these techniques have fostered the development of high-through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Recently, a bacterial metabolic perturbation has emerged as an indicator of antibiotic efficacy because bacterial metabolism plays an important role in reflecting their viability, growth, and reproduction, and antibiotics directly induce metabolic changes in biofilms. [43][44][45][46] Many reports demonstrated the interplay among action mechanisms of antibiotics, bacterial metabolism, and eventually their growth inhibition. 47,48 For the rapid phenotypic AST, such metabolic changes have recently been monitored by measuring redox interactions of labeled reporters which are involved in bacterial respiration, pH change, and enzyme production during bacterial metabolism.…”
Section: Combined Electrical-electrochemical Monitoring For Antibioti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a bacterial metabolic perturbation has emerged as an indicator of antibiotic efficacy because bacterial metabolism plays an important role in reflecting their viability, growth, and reproduction, and antibiotics directly induce metabolic changes in biofilms. [43][44][45][46] Many reports demonstrated the interplay among action mechanisms of antibiotics, bacterial metabolism, and eventually their growth inhibition. 47,48 For the rapid phenotypic AST, such metabolic changes have recently been monitored by measuring redox interactions of labeled reporters which are involved in bacterial respiration, pH change, and enzyme production during bacterial metabolism.…”
Section: Combined Electrical-electrochemical Monitoring For Antibioti...mentioning
confidence: 99%
“…46,[49][50][51] Although those label-based metabolic sensing techniques are successful as a rapid and user-friendly AST approach, there is a growing interest in developing a label-free AST technique because of its overwhelming advantages including simplified steps, reduced amounts of reagents, point-of-care realization, and costeffectiveness. 45,52 For the label-free metabolic sensing, our group demonstrated that the electrons metabolically produced from Pseudomonas aeruginosa can be a strong signal to monitor their growth and treatment efficacy, successfully providing a quantifiable MIC of three antibiotics (i.e., gentamicin, ciprofloxacin, and ampicillin), and characterized the bacterial antibiotic action mechanisms. [53][54][55] A microbial fuel cell (MFC) was created as a metabolic biosensor where the anode incubated the pathogen with antibiotics.…”
Section: Combined Electrical-electrochemical Monitoring For Antibioti...mentioning
confidence: 99%